MODELING OF PROCESS OF CONSTRUCTING 3D IMAGES BY DYNAMIC SEQUENCE OF 2D IMAGES - Igor S. Konstantinov, Ilya А. Koskin, Sergey A. Lazarev, Yuriy N.Maslakov,Vitaliy A.Gaivoronskiy (International Journal of Advanced Science and Technology, 2020)
This article discusses the process of constructing stereo images by dynamic sequence of plain images, received with a moving camera. Various mathematical models can be used; some of the models can be implemented with a number of algorithms. Resulting quality of stereo image depends on the combination of models and algorithms. The principles of system modeling of the process are considered. Features of constructing a parametric, modeling and quality control modules are discussed. The main scope is a modeling module. Suitable mathematical models are classified. Models are matched with solution methods. Materials of this article can be used to build an automated system of real-time high quality 3D-models building, based on a sequence of 2D images.